MONOPOLAR DIATHERMY AS COMPARED TO SILK LIGATURES FOR PER OPERATIVE HAEMORRHAGE CONTROL DURING TONSILLECTOMY: Pre operative Haemorrhage Control During Tonsillectomy - Ayub, Zeeshan; Ahmed, Bashir (Pakistan Armed Forces Medical Journal, 2009)
Objective: To determine whether monopolar diathermy is a better tool for haemostasis compared to tying of silk ligatures. Study Design: Quasi-experimental study. Place and Duration of Study: The study was done in ENT department of Combined Military Hospital Rawalpindi from July 2006 to March 2007. Patients and Methods: Seventy patients were included in this study and were divided into two groups of thirty-five each; one group underwent tonsillectomy with monopolar diathermy for haemorrhage control and tying of silk ligatures for hemostasis in second group. Chi square test was used as the test of significance. Results: Monopolar diathermy is shown to be a better method of haemorrhage control as compared to tying of silk ligatures (p-value <0.05). Conclusions: These results demonstrate the effectiveness of monopolar diathermy as a coagulation tool.